Predictors of return to work with and without restrictions in public workers - Dias, Adriano [UNESP] (2019)
Background Sick leaves are important events for both the worker and the employer. Many factors are related with sick leaves and depending on the factors the worker could perform a successful return to work. In this sense, the objective of this study is to identify those factors associated with return to work after sick leaves in a group of public workers in Brazil. Methods A case-control study of return to work after sick leaves in a university campus from 2010 to 2015. Logistic regression models were adjusted for two different response variables: return to work with and without restrictions. A digital database was created and completed with data from manual sources. Results A computerised database has been created, based on manual records, which has allowed us to identify labour and non-labour factors associated with the return to work after a sick leave and the possible functional readaptation, with or without restrictions, in public workers. Age at the beginning of the process, number of sick leaves, those of more than 16 days, average duration (total time of sick leaves / number of medical records), and mid-level healthcare positions were associated with return to work without restrictions. In the model of return to work with restrictions, the age of hiring by the university, the number of sick leaves, those of more than 16 days, and mid-level healthcare positions, both rural work and operational positions, were associated to the response variable. Conclusions This study has allowed us to identify the factors associated with the return to work after a period of sick leave in a large group of public workers. However, more research is needed on the mental disorders that cause sick leaves, their evaluation and the handling of these situations.